Balanced Scorecard Sebagai Sistem Manajemen Strategi dalam Mengukur Kinerja Perusahaan - Herawati, Heny; Yulia, Rasty (Akuisisi : Jurnal Akuntansi, 2024)
This research aims to determine the performance of PT Sarana Bhuana Jaya when measured by the Balanced Scorecard. This type of research is a case study. The data analysis techniques used to answer the problem formulation include using Net Profit Margin, Return On Investment, Return On Equity, and Multiattribution Attitude Model analysis. Based on the research results, it shows that the business strategy, when measured by the Balanced Scorecard, has good performance. PT Sarana Bhuana Jaya's financial perspective is not effective because the Net Profit Margin, Return On Investment, and Return On Equity in 2019 are smaller than in 2018 and 2017. This means that the company's ability to generate profits is not effective. PT Sarana Bhuana Jaya's customer perspective, when measured by the Balanced Scorecard, has good performance. The customer perspective, when measured by the Balanced Scorecard, shows good performance. The internal business process perspective, when measured by the Balanced Scorecard, has good performance. Growth perspective and when measured by the Balanced Scorecard the performance is good.